Bioengineered three-dimensional physical constructs from quince seed mucilage for human adipose-derived mesenchymal stem cells. (May 2020) - Şimşek, Ekin; Karaca, Burak; Arslan, Yavuz Emre
In this study, we aimed at fabricating a novel porous physical construct from quince seed mucilage for translational medicine applications. To achieve this goal, quince seed mucilage was extracted, molded, and freeze-dried. After being freeze-dried, the molded constructs were chemically crosslinked with 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide/N-hydroxysuccinimide to maintain the mechanical integrity of the structure. The fabricated scaffolds were characterized in-depth by scanning electron microscopy, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller analysis, thermogravimetric analysis, and dynamic mechanical analysis in addition to the swelling, liquid uptake, and porosity tests. The extraction yield of mucilage was calculated to be 6.28% ± 0.40% (n = 3). The swelling ratio of crosslinked quince seed mucilage–derived scaffolds was found to be 12, 677.50% ± 388.82% (n = 3), whereas the porosity of crosslinked quince seed mucilage–derived scaffolds was 83.43% ± 2.84% (n = 3). The analyses confirmed the crosslinked quince seed mucilage–derived scaffolds to be possessed interconnected, highly porous structure. Afterward, human adipose-derived mesenchymal stem cells were seeded on the crosslinked quince seed mucilage–derived scaffolds, and the cell viability on the scaffolds was assessed with 3-[4, 5-dimethylthiazole-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. The MTT results revealed the scaffolds not to be possessed any cytotoxic effect on seeded cells. Human adipose-derived mesenchymal stem cells adhesion and migration on the crosslinked quince seed mucilage–derived scaffolds were also evaluated histologically using hematoxylin and eosin staining in addition to scanning electron microscopy analysis. In conclusion, we believe that crosslinked quince seed mucilage–derived scaffolds have the potential to be an alternative to routinely used polysaccharides in regenerative medicine applications.